Improved dairy production through enzyme supplementation - SHAKYA, JYOTI; BALHARA, A K; DAHIYA, S S; LAILER, P C; SINGH, INDERJEET (The Indian Journal of Animal Sciences, 2019)
The rumen ecosystem has the ability to transform low grade nutrients to high quality products owing to the numerous micro-flora colonies it harbours which produce different types of degrading enzymes. It has been assumed that normal rumen flora is able to digest only a small portion of the cellulosic biomass enteric rumen. This provides numerous opportunities for improving digestion via enhancing digestibility through degradation pathways in rumen. The modern animal nutrition science has utilized this knowledge to commercially harness enzymes for improving nutrient availability for production enhancement. Broadly categorized as fibrolytic, proteolytic and amylolytic, these enzymes act synergistically with the naturally available enzymes in rumen. Enzyme supplementations improve the digestibility of fibre and increase nutrient absorption and energy availability for production activities across physiological status of the animal. This review summaries response of large lactating ruminants to the external enzyme (in vivo) supplementation in terms of actual milk production, milk composition, body weights, dry matter intake and digestibility of nutrients, as well as to assess the economic benefit in terms of additional expenses incurred and benefit derived with increase in milk production.